Flavonoids as modulators of gut-liver axis: emerging therapeutic strategies for MAFLD - Hao, Mengxuan; Wang, Zihui; Wang, Liren; Yimamu, Aidiya; Su, Xiaoling; Zhang, Minmin; Li, Xincan; Zhang, Quanlong; Sun, Zeyu (Frontiers in Pharmacology, 2025)
Metabolic dysfunction-associated fatty liver disease (MAFLD) is a significant global health challenge affecting approximately 25% of adults worldwide. Given the limited efficacy of existing therapies, there is an urgent need for novel treatment strategies. Flavonoids, a diverse class of natural polyphenolic compounds, exhibit significant potential in ameliorating MAFLD by modulating hepatic lipid metabolism and immune-inflammatory responses via gut-liver axis. This review systematically explores the interactions between flavonoids and gut microbiota, elucidating their role in MAFLD progression. We highlight how flavonoid structural diversity and microbial biotransformation modulate multiple key pathways, such as PPARα, PPARγ, ERβ, Nrf2, NF-κB, and FXR signalling. These multi-target mechanisms underpin the therapeutic potential of flavonoids in reducing lipid accumulation, oxidative stress, inflammation, and fibrosis in MAFLD. We also discuss innovative strategies, including flavonoid-probiotic synergies, nanotechnology-enhanced delivery systems, and personalized nutrition strategies. By integrating evidence from preclinical models and clinical trials, we highlight the translational potential of flavonoid-based interventions for MAFLD management. Our analysis underscores flavonoids as multi-target, safe and effective solutions for MAFLD management, warranting further clinical studies to translate these findings into routine clinical practice.